2012
DOI: 10.1016/j.cell.2012.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Membrane Bending by the N-BAR Protein Endophilin

Abstract: Functioning as key players in cellular regulation of membrane curvature, BAR-domain proteins bend bilayers and recruit interaction partners through poorly understood mechanisms. Using electron cryomicroscopy, we present reconstructions of full-length endophilin and its N-terminal N-BAR domain in their membrane-bound state. Endophilin lattices expose large areas of membrane surface, and are held together by promiscuous interactions between endophilin's amphipathic N-terminal helices. Coarse-grained molecular dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
319
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(345 citation statements)
references
References 49 publications
23
319
3
Order By: Relevance
“…Contrary to the prevailing picture of BARs on membranes, in our simulations the proteins initially aggregate in the areas of negative Gaussian curvature, i.e., in troughs. The crescent shape (28) of BARs and the way they coat tubules (14) are what has motivated the perception of them populating positively curved membrane regions. Although single N-BAR proteins were observed in the present simulations to readily explore convex areas of the membrane, it appears that the quasi-linear aggregates have very different curvature proclivities at early stages of membrane remodeling.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Contrary to the prevailing picture of BARs on membranes, in our simulations the proteins initially aggregate in the areas of negative Gaussian curvature, i.e., in troughs. The crescent shape (28) of BARs and the way they coat tubules (14) are what has motivated the perception of them populating positively curved membrane regions. Although single N-BAR proteins were observed in the present simulations to readily explore convex areas of the membrane, it appears that the quasi-linear aggregates have very different curvature proclivities at early stages of membrane remodeling.…”
Section: Resultsmentioning
confidence: 99%
“…1073/pnas.1309819110/-/DCSupplemental. a single protein or dense N-BAR lattices were studied theoretically and experimentally (14,(23)(24)(25)(26), simulating the N-BAR protein behavior at low and intermediate surface densities provides microscopic insights into the transient structures during the membrane restructuring at physiologically relevant concentrations. This is especially important in light of recent experimental work revealing the difference in mechanics of membrane bending under low-and high-density regimes of N-BAR proteins (27) and showed that N-BAR's mode of action needs to be studied with precise control of the bound protein density.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Generating curvature in a phospholipid bilayer implies that some form of packing asymmetry exists between the two leaflets of the membrane (Kirchhausen 2012). In principle, there are at least four ways in which cytosolic EAPs may contribute to lipid asymmetry and membrane curvature during CCP invagination: (1) by locally clustering lipids with larger-than-average head groups through interaction with membrane-associated proteins (Zimmerberg and Kozlov 2006), by converting one lipid type to another (Kooijman et al 2003) or by actively transporting a lipid type(s) from one leaflet to the other (Rauch and Farge 2000;Roelants et al 2010); (2) by "floating" an amphipathic helix in the inner leaflet of the membrane (Ford et al 2002) or by inserting a hydrophobic loop into the inner leaflet of the membrane (Plomann et al 2010); (3) by association of a precurved membrane-binding protein domain (such as BAR, F-BAR, or i-BAR) with the membrane surface (Mim et al 2012); or, most simply, (4) by membrane-associated protein crowding (Stachowiak et al 2012). The different mechanisms for generating membrane curvature are summarized in Figure 2.…”
Section: Coat Maturation and The Propagation Of Membrane Curvaturementioning
confidence: 99%